Morfología del cariotipo de Luma apiculata (DC.) Burret (Myrtaceae) - JARA-SEGUEL, PEDRO; CÁRCAMO-FINCHEIRA, PAZ; PALMA-ROJAS, CLAUDIO; VON BRAND, ELISABETH (Gayana Botánica, 2013)
Luma apiculata (DC.) Burret, had a symmetric karyotype, with 2n = 22 small sized chromosomes, ranging between 2.2 ?m and 0.8 ?m. The haploid karyotype formula was 9m + 2sm = 11. These karyotype characteristics of L. apiculata are a common character within Myrtaceae.